New records of Aphrogenia alba Kinberg, 1856 from Brazilian waters: a rare Aphroditidae species - Craveiro, Nykon; De Almeida, F.; Rosa Filho, J. (Latin American Journal of Aquatic Research, 2019)
This paper reports the occurrence of Aphrogenia alba in Potiguar Basin, northeastern Brazil. The specimen was sampled at a depth of 180 m off the Rio Grande do Norte coast in the muddy bottom. This new record extends, after 37 years, the known geographic distribution of the species in the Brazilian coast, which had previously been recorded between Rio de Janeiro (Cabo de São Tomé and Ilha Grande) and Rio Grande do Sul.